Real-time observation of polymerase-promoter contact remodeling during transcription initiation. Issue 1 (December 2017) - Meng, Cong; Fazal, Furqan; Block, Steven
Abstract Critical contacts made between the RNA polymerase (RNAP) holoenzyme and promoter DNA modulate not only the strength of promoter binding, but also the frequency and timing of promoter escape during transcription. Here, we describe a single-molecule optical-trapping assay to study transcription initiation in real time, and use it to map contacts formed between σ70 RNAP holoenzyme fromE. coli and the T7A1 promoter, as well as to observe the remodeling of those contacts during the transition to the elongation phase. The strong binding contacts identified in certain well-known promoter regions, such as the −35 and −10 elements, do not necessarily coincide with the most highly conserved portions of these sequences. Strong contacts formed within the spacer region (−10 to −35) and with the −10 element are essential for initiation and promoter escape, respectively, and the holoenzyme releases contacts with promoter elements in a non-sequential fashion during escape. Contacts between RNA polymerase and promoter DNA modulate the strength of binding and the frequency of promoter escape during transcription. Here, the authors describe a single molecule optical-trapping assay to study transcription initiation and observe the dynamic remodeling of enzyme contacts in real time.